(untitled) (Research, Society and Development, 2022)
Introduction: Cancer is one of the main causes of morbidity and mortality in the world, annually registering approximately 10 million new cases and 6 million deaths. In Brazil, neoplasms are the third leading cause of death in the population. Objective: This study is a cross-sectional analysis with the objective of characterizing the incidence of breast cancer in the female population during the pandemic. Methodology: The Datasus Oncology panel was used for the period from 2018 to 2021, women between 35 and 39 years old with malignant breast cancer, from the states of Bahia (BA) and Rio Grande do Norte (RN). Results: The results of the present study contributed to verifying the decrease in the number of diagnosed cases of cancer due to several factors such as anxiety, stress and especially the social isolation imposed by the pandemic. Conclusion: It was shown that the pandemic made it difficult to access routine and preventive exams for the diagnosis of this, which is a leader in lethality.